Health and Well-Being Measures of Collegiate Athlete and Non-Athlete Graduates - J.D. DeFreese; Erianne Weight; Zachary Kerr; Emily Kroshus (University of Kansas Libraries, 2021)
American collegiate sport participation has been linked with psychosocial and career-related benefits as well as with mental and physical health risks, with extant research on this topic revealing mixed results. The study purpose was, informed by the Health through Sport Conceptual Model, to describe and compare associations among health related quality of life and psychosocial measures of former U.S. collegiate athletes and non-athletes from four university graduation cohorts. Results suggest on aggregate former collegiate athletes report more positive measures than their non-athlete peers. Study findings were, in some instances, mitigated/reversed when participants endorsed concussion, career ending injury or revenue sport participation histories or were female. Though limited by a cross-sectional design and a potential health worker effect, results provide some support for protective associations of collegiate athletics participation. This study also provides a theoretical bridge from intercollegiate athletics participation to broader sport promotion literatures.